Evaluation of pressure changes for capillary and fishbone valves in Lab-on-CD systems - Peyman, J.; Akbar Nozari, A.; Soin, N.; Ibrahim, F. (2009)
This paper describes an investigation in Capillary and Fishbone valves as controlling medium of liquid flow for microdevices and diagnosis methods like Enzymed Linked Immonusorbent Assays (ELISA). Numerical simulation by MATLAB programming was employed to predict the pressure gradient at the Capillary valve expansion part and Fishbone valve section. The analysis results of pressure gradient versus channel width values depicted that an increase in the width of channel leads to a decrease in the pressure gradient. While an increase in Surface tension raises up the required pressure gradient for both valves. Pressure gradient sensitivity to contact angle between liquid and gas in the Capillary valve is more than the Fishbone valve.